Philological Investigation of Some English Common Plant Names. - Tayade, S K; Patil, D A (Plantae Scientia, 2019)
This communication is aimed at the scientific study of the genesis and development of common plant names as used in the English language. Every human society, whether primitive or advanced has own vocabulary developed on their observations, experience, sentiments, dogmas and customs. Every human society tries to classify and name plants in his ambience and thereby mankind celebrates the biodiversity of his time. The present authors investigated total of 79 plant species belonging to 78 genera and 53 families of angiosperms, one species being a gymnosperm. They divulged as many as 13 bases on which the common plant names in English are coined. They obviously reveal the richness and heritage of English people. The knowledge and wisdom of ancient will be certainly helpful for human welfare